THE ROLE OF THE SPN TRADE UNION LEADER IN RESOLVINGAN CONFLICT BETWEEN WORKERS AND THE LEADER OF PT. PARKLAND WORLD INDONESIA - Dian Siska Pertiwi; Ahmad Toni; April Laksana (SEAN Institute, 2022)
The company or employer is part of the ring of the wheels of the country's economy. Labor is a vital asset in the company in addition to money. Workers or laborers are human beings who use their labor and ability to get retribution in the form of income, either in the form of money or other forms from employers or employers. The industrial era can potentially cause increasing and complex industrial relations problems. The working relationship between workers and employers is not always harmonious. The maintenance of relations between workers, trade unions and management within the scope of industrial relations is essential to prevent conflicts in the world of work, if not resolved immediately, it can lead to industrial relations disputes due to the disharmony of relations between these parties. This research uses a qualitative approach with a case study methodology in the field of various existing case studies with a perception of taking material from several sources. Qualitative case studies as research that uses empirical evidence from one or more organizations and researchers seek to study the problem in context—trade union PT. Parkland World Indonesia uses conflict approach and management techniques in dealing with conflicts between individual workers and personal leaders, to facilitate SPN in mediation and assistance in conflict resolution.